Der unterdrückte Sexus : historische Texte und Kommentare zur Homosexualität - Hohmann, Joachim S.; Borneman, Ernest; Wagner, Thomas (Lollar : Andreas Achenbach, 1977)
Fonds Suzan Daniel (FSD)
Duits
Monografie